2011
DOI: 10.1155/2011/971938
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Nuclear Receptor Signaling, and Anti-Inflammatory Pathways

Abstract: There is increased investigation of the human microbiome as it relates to health and disease. Dysbiosis is implicated in various clinical conditions including inflammatory bowel disease (IBD). Probiotics have been explored as a potential treatment for IBD and other diseases. The mechanism of action for probiotics has yet to be fully elucidated. This paper discusses novel mechanisms of action for probiotics involving anti-inflammatory signaling pathways. We highlight recent progress in probiotics and nuclear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 157 publications
1
54
0
2
Order By: Relevance
“…Thirty-one patients accomplished the trial (17 males, median age 13 year, range [7][8][9][10][11][12][13][14][15][16][17][18]. Mayo score (including clinical and endoscopic features) decreased significantly in the L. reuteri group (3.2 AE 1.3 vs. 8.6 AE 0.8, P < 0.01) compared with placebo (7.1 AE 1.1 vs. 8.7 AE 0.7, NS); furthermore, histological score significantly decrease only in the L. reuteri group (0.6 AE 0.5 vs. 4.5 AE 0.6, P < 0.01) (placebo: 2.9 AE 0.8 vs. 4.6 AE 0.6, NS).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one patients accomplished the trial (17 males, median age 13 year, range [7][8][9][10][11][12][13][14][15][16][17][18]. Mayo score (including clinical and endoscopic features) decreased significantly in the L. reuteri group (3.2 AE 1.3 vs. 8.6 AE 0.8, P < 0.01) compared with placebo (7.1 AE 1.1 vs. 8.7 AE 0.7, NS); furthermore, histological score significantly decrease only in the L. reuteri group (0.6 AE 0.5 vs. 4.5 AE 0.6, P < 0.01) (placebo: 2.9 AE 0.8 vs. 4.6 AE 0.6, NS).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies, as discussed above, have shown that probiotics increase barrier function in terms of increased mucus, antimicrobial peptides, and sIgA production, competitive adherence for pathogens, and increased TJ integrity of epithelial cells. Current investigation into the mechanism of action of specific probiotics has focused on probiotic-induced changes in the innate immune functions involving TLRs and its downstream systems Like NF-κB, and other pathways (Yoon and Sun, 2011). Although the immunomodulatory effects of probiotics have been demonstrated in experimental animal models of allergy, autoimmunity, and IBD, information from clinical trials in humans is scarce.…”
Section: Resultsmentioning
confidence: 99%
“…Altered immune responses are among the elements related to the pathogenesis of inflammatory bowel disease (IBD), and mounting evidence indicates that the NF-B signaling pathway plays a major role in inflammatory responses, making the pathway a potential target in therapy (2). NF-B, initially sequestered in the cytoplasm and whose release upon activation of the signaling cascade allows free NF-B translocation into the nucleus, plays the role of a transcriptional regulator of genes involved in inflammatory processes (3).…”
mentioning
confidence: 99%